Asthma Nursing Care Management and Study Guide - Piotr Pawłowski; Marta Łopuszyńska; Beata Korpornicka; Klaudia Jakubowska; Dorota Nalepa (Kazimierz Wielki University, 2017)
Introduction and purpose of the work. Bronchial asthma is one of the most endangering civilizational diseases of the 21st century. Studies show that the number of patients with bronchial asthma around the world is 300 million and it is constantly increasing. The actions taken by the nurse towards the patient depend on the duration period of the disease and the health condition of the patient, as well as the range of the expected aid. The aim of all those actions is supporting and aiding the patient to gain and sustain an optimal level of functioning with the disease in everyday life. Defining the types of actions that ought to be taken by the nurse towards the patient suffering from bronchial asthma. Material and method. A case study method was applied. A modified guide for collecting patient data was used, the scale according to Dutch Consensus Prevention of Bedsores (CBO), Barthel scale, the ACTTM - Asthma Control Test as well as the author's test that verifies the patient's skills and knowledge in the preparation for self-care. Results and conclusions. To reduce the risk of the disease exacerbations the nurse can suggest the patient some methods of the elimination of allergens from the environment as well as introduce and teach her the methods of stress management, because these are the main problems in the patient that can lead to the exacerbation of the disease. The main tasks of the nurse in educating the patient are the eradication of knowledge deficiencies related to the PEF self-control and the elimination of allergens.